Students’ Perceptions on Learning Management Systems of Arabic Learning through Blended Learning Model - Taufiqurrochman, R.; Muslimin, Imam; Rofiki, Imam; ABAH, Joshua Abah (Universitas Islam Negeri Raden Intan Lampung, 2020)
The emergence of various Learning Management System (LMS) applications support the implementation of Arabic learning with a blended learning model that combines traditional method (face to face) and online. The purpose of this study is to describe students’ perceptions as users of the LMS application. The study was descriptive research. As many as 150 students involved in this study, 75 percent chose the blended learning model for learning Arabic. They called the ten most popular LMS application platforms such as Google Classroom, Edmodo, Schoology, Geschool, Our Class, Kelase, ClassDojo, TrackCC, Class123, and Eckovation. Of the 10 LMS applications, the best is Edmodo and the most famous is the Google Classroom. The potential of the LMS application as a representation of the blended learning model is because it has a variety of features. There are at least 16 features, namely: integration of LMS applications with social media, communication features with parents, attendance, payment, homework, conferences, forums, certificates, quiz (polling), document shares, grade books, announcements, testing/surveys, calendar/schedule, email, and chat facilities. The results of students' perceptions regarding these features indicate that they understand all the functions of the LMS features. About learning Arabic, they assessed that all LMS applications had the potential to be used for learning Arabic. The most significant potential is the ability of the LMS application to help learn speaking, writing, and grammar (Sharaf and Nahwu) skills.